2016
DOI: 10.3389/fphys.2016.00457
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Mouse Model of Emphysema Induced by Multiple Instillations of Low-Dose Elastase

Abstract: Many experimental models have been proposed to study the pathophysiological features of emphysema, as well as to search for new therapeutic approaches for acute or chronically injured lung parenchyma. We aimed to characterize an emphysema model induced by multiple instillations of elastase by tracking changes in inflammation, remodeling, and cardiac function after each instillation. Forty-eight C57BL/6 mice were randomly assigned across two groups. Emphysema (ELA) animals received 1, 2, 3, or 4 intratracheal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 63 publications
6
38
0
Order By: Relevance
“…Both models may result in cachexia [ 39 ] and pulmonary hypertension [ 40 ], but the lung damage induced by elastase persists for longer after induction in contrast to cigarette smoke [ 41 ]. In addition to lung structural damage induced by PPE, a persistent lung inflammatory process [ 42 ] with elastolysis and fibrogenesis has been observed [ 32 ]. The specific elastase-induced emphysema protocol used in the present study has been shown to produce loss of lean and total body mass, likely suggesting cachexia [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both models may result in cachexia [ 39 ] and pulmonary hypertension [ 40 ], but the lung damage induced by elastase persists for longer after induction in contrast to cigarette smoke [ 41 ]. In addition to lung structural damage induced by PPE, a persistent lung inflammatory process [ 42 ] with elastolysis and fibrogenesis has been observed [ 32 ]. The specific elastase-induced emphysema protocol used in the present study has been shown to produce loss of lean and total body mass, likely suggesting cachexia [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sample size calculation was based on pilot studies and on previous studies in a murine model of elastase induced emphysema conducted in our laboratory [ 26 , 27 , 29 , 31 , 32 ]. A sample size of ten animals per group would provide the appropriate power (1 − β = 0.8) to identify significant (α = 0.05) differences in mean linear intercept between C and ELA groups, taking into account an effect size d = 1.97, a two-sided test, and a sample size ratio = 1 (G * - Power 3.1.9.2, University of Düsseldorf, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…To the best of our knowledge, this was the first investigation of the effects of different levels of V T variability on pulmonary and cardiovascular function, lung morphometry, and gene expression of markers of inflammation, surfactant proteins, epithelial cell damage, cell mechanical stress, and fibrogenesis in experimental emphysema. We chose the repeated intratracheal elastase instillation model because it reproduces important features of emphysema, including deterioration of respiratory system mechanics, airspace enlargement, and lung inflammation (Antunes and Rocco, 2011 ; Cruz et al, 2012 ; Henriques et al, 2016 ; Oliveira et al, 2016 ; Padilha et al, 2016 ; Rocha et al, 2017 ; Suki et al, 2017 ). Furthermore, multiple elastase instillations can lead to cardiorespiratory alterations (Antunes et al, 2014 ) that are consistent with cor pulmonale , including increased RV afterload (Henriques et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Circulating procollagen peptides are elevated following COPD exacerbations, consistent with active collagen synthesis (51). When administered intratracheally to mice, porcine pancreatic elastase increases rather than decreases collagen (14,42), particularly in regions of emphysema. Other studies suggest that a nonuniform distribution of collagen produces mechanical forces, which propagate emphysema after inflammation abates (17).…”
Section: Introductionmentioning
confidence: 93%